Vegetative propagation of black mulberry (Morus, nigra L) recommended for landscaping roads and city streets - Ubaidullaev Farkhod Bakhtiyarullaevich; Khaitov Farhod Juraevich Assistant; Majidov Abdulaziz Norqobilovich (Zien Journals, 2023)
Today, special attention is paid to the identification of highly decorative, promising plant species that are resistant to various external harmful factors, and the development of effective and optimal methods for rapid reproduction as priorities for landscaping roads. In this regard, representatives of the mulberry (Morus, nigra L) have a wide decorative potential, the development of fast and effective methods of propagation from seeds and vegetative propagation, the evaluation of the effectiveness of use in landscaping is of great scientific and practical importance.
Keywords: scientific; propagation; evaluation; effectiveness